Kemampuan berpikir kreatif mahasiswa dalam memecahkan masalah sistem persamaan linier ditinjau dari brain dominance - Lusiana, Restu; Andari, Tri (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
Students' creative thinking processes need to be developed to support them in solving complex mathematical problems, but this is not easy. This study aims to describe students' creative thinking skills in solving linear equation system problems based on brain dominance. This research is a qualitative descriptive research with a case study approach. Subjects were categorized into right brain dominance and left brain dominance by using a brain dominance questionnaire. The research instruments were in the form of tests and interview guidelines. Data validation uses method triangulation and data is analyzed through data reduction, data presentation, data verification, and drawing conclusions. The results showed that the subject of right brain dominance in fluency gave 3 responses, in flexible thinking the subject gave 3 different ideas, in original thinking the subject gave a unique response, and in elaboration the subject did not show a coherent answer. While the left brain dominant subject in fluent thinking (fluency) gave 4 responses, in flexible thinking the subject gave 3 general ideas, in original thinking the subject did not show a unique response, and in detailed thinking (elaboration) the subject showed a flurry of answers.